Students’ Perceptions of the Use of Social Media in French Languages Learning - Sandy Lesmana; Tika Zuleika; Vita Kusumaningtyas (International Journal of Education, Information Technology, and Others, 2026)
Rapid technological advancements, coupled with developments in science, have made knowledge easier to access and search for. One example of this ease of accessing and seeking knowledge in the world of education is the use of digitalisation. Digitalisation can support the learning process through digital media. One form of digitalisation in education involves the use of social media by students in the learning process, particularly in the context of learning French. This study aims to analyse the opinions of third-semester students on the French Language Programme at the Faculty of Languages, Arts and Culture, Yogyakarta State University, regarding the use of social media in the French language learning process. The object of this study is questionnaire data regarding the perceptions of students in the French Language Study Programme regarding the use of social media in the learning process. The data collection method used in this study is the TAM (Technology Acceptance Model) method. The five indicators within the TAM method used in this study are ACU (Actual System Usage), PU (Perceived Usefulness), PEOU (Perceived Ease of Use), ATU (Attitude Toward Use), and BI (Behavioural Intention to Use). The research instrument used was a Likert scale with five response levels: 1 = Strongly Disagree, 2 = Disagree, 3 = Somewhat Agree, 4 = Agree, 5 = Strongly Agree. The results of this study indicate that the highest percentage for the ACU (Actual System Usage) indicator was “Agree” at 46.4%, for PU (Perceived Usefulness) it was “Agree” at 51.47%, PEOU (Perceived Ease of Use) was “Agree” at 42.40%, ATU (Attitude Toward Use) was “Agree” at 45.7%, and BI (Behavioural Intention to Use) was “Agree” at 50%. Respondents agreed that the use of media in the French language learning process can help students develop their French language skills. This study can contribute to understanding the use of social media to assist students in the French language learning process and can provide insights into the utilisation of technology in foreign language learning, particularly French.